2015
DOI: 10.5306/wjco.v6.i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastatic disease, the curative challenge in radiation oncology

Abstract: The concept of oligometastatic disease was first described by Hellman and Weichselbaum in 1995. The mere insight of this concept led to the hypothesis that this disease may be cured using local ablative weapons. Surgery has already demonstrated this hypothesis. Surgery limitations, either technical or due to refusal or associated comorbidity, have led to implement alternative ablative options such as stereotactic body radiation therapy (SBRT). SBRT evolved from (stereotactic radiosurgery) because of the need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The development of effective chemotherapy regimens and combinations of systemic and local treatments has improved the prognosis of metastatic cancer patients . After the concept of oligometastases was proposed, several studies have reported that aggressive local treatment of oligometastatic lesions may improve patient survival . For example, the National Comprehensive Cancer Network guideline recommends local treatment for pulmonary metastases arising from colon cancer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of effective chemotherapy regimens and combinations of systemic and local treatments has improved the prognosis of metastatic cancer patients . After the concept of oligometastases was proposed, several studies have reported that aggressive local treatment of oligometastatic lesions may improve patient survival . For example, the National Comprehensive Cancer Network guideline recommends local treatment for pulmonary metastases arising from colon cancer …”
Section: Introductionmentioning
confidence: 99%
“…2,3 After the concept of oligometastases was proposed, several studies have reported that aggressive local treatment of oligometastatic lesions may improve patient survival. [4][5][6][7] For example, the National Comprehensive Cancer Network guideline recommends local treatment for pulmonary metastases arising from colon cancer. 8 However, the criteria for selecting the patients for whom local treatment is appropriate have not yet been defined, particularly as metastatic cancer patients usually experience distant site failure.…”
Section: Introductionmentioning
confidence: 99%
“…If oligometastatic disease is eradicated using local ablative procedures, patients may be cured. 39 This hypothesis has been supported by studies reporting that patients with oligometastatic disease after radical surgical resection have 5-year survival rates of 30%–50%. 2 , 18 , 19 …”
Section: Resultsmentioning
confidence: 88%
“…Despite excellent local control rates, out-of-field metastatic progression (out-of-field hepatic metastases and extrahepatic metastases) develops in a substantial proportion of patients after SBRT. 8 , 9 , 39 Currently, the selection of patients for SBRT is based on clinical criteria only. Therefore, it seems essential to improve the selection of patients with liver metastases for SBRT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation